Management Practices of School Heads, Organizational Behavior, and Performance of Teachers in Distance Learning Environment - Starsky M. Buitizon (Research Synergy Foundation, 2021)
This study determined the management practices of school heads, organizational behavior, and performance of teachers in the distance learning environment. Fifty-five (55) public school principals and one thousand five hundred seven (1507) teachers were the respondents of the study. The researcher utilized the descriptive-correlational examination plan, which utilized the adopted and modified questionnaires to assess and measure the variables under study. The statistical tools used to analyze the data gathered were: Frequency and Percentage, Mean, Standard Deviation, and Multiple Linear Regression Analysis. Findings revealed that the management practices, organizational behavior, and performance of teachers were relevant to the distance learning environment. The findings were used to determine the strategic plan model to be proposed by the DepEd and school officials. Since the school heads' management practices are assessed to a high extent, it may be sustained by introducing innovations in their respective stations, which will focus on how the instructional programs may be carried out to achieve the vision, mission, and goals of the DepEd. This may be done by involving the teachers in the instructional decisions to be made as well as in crafting the different plans to be implemented in the school context. The teachers may be exposed to seminars and capability building to further enhance their teaching pedagogy as well as their skills in the different aspects of the instructional program in the context of the new normal in the educational system.